2016
DOI: 10.1371/journal.pone.0159725
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Direct Access to Tests to Investigate Cancer: A Survey of English General Practitioners

Abstract: BackgroundThe 2015 NICE guidelines for suspected cancer recommend that English General Practitioners have direct access to diagnostic tests to investigate symptoms of cancer that do not meet the criteria for urgent referral. We aimed to identify the proportion of GPs in England with direct access to these tests.MethodsWe recruited 533 English GPs through a national clinical research network to complete an online survey about direct access to laboratory, radiology, and endoscopy tests in the three months leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…19 At that time, a survey of GPs showed that investment was required to achieve DA to these tests across all English regions in order to reduce the intervals between request, testing, and reporting. 20 GPs reported good access to X-ray and laboratory investigations, apart from faecal occult blood testing and urine protein electrophoresis, whereas two-thirds had DA to gastroscopy, half to CT, and one-third to colonoscopy. Excluding X-ray, less than one-fifth of GPs could access radiology and endoscopy within the timescales recommended by NICE.…”
Section: Introductionmentioning
confidence: 99%
“…19 At that time, a survey of GPs showed that investment was required to achieve DA to these tests across all English regions in order to reduce the intervals between request, testing, and reporting. 20 GPs reported good access to X-ray and laboratory investigations, apart from faecal occult blood testing and urine protein electrophoresis, whereas two-thirds had DA to gastroscopy, half to CT, and one-third to colonoscopy. Excluding X-ray, less than one-fifth of GPs could access radiology and endoscopy within the timescales recommended by NICE.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation of GPs’ low awareness of the guidance may relate to the existing low access to faecal occult blood tests (~54%) compared with other direct laboratory tests provided in primary care such as Ca125 which had 100% access across England 24…”
Section: Discussionmentioning
confidence: 99%
“…In England, there are guidelines on direct access and on waiting times for investigations of suspected cancer in primary care (National Institute for Health and Care Excellence (NICE) ), which are based on investigating where the risk of cancer may be 3% or higher, compared to earlier guidelines based on a 5% threshold. A recent survey in England showed that few GPs could access tests such as radiology and endoscopy within these time guidelines (Nicholson, Oke, Rose, & Mant, ). Patients generally support investigations at even lower thresholds (Banks et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…which are based on investigating where the risk of cancer may be 3% or higher, compared to earlier guidelines based on a 5% threshold. A recent survey in England showed that few GPs could access tests such as radiology and endoscopy within these time guidelines (Nicholson, Oke, Rose, & Mant, 2016). Patients generally support investigations at even lower thresholds (Banks et al, 2014).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%